Study on Standardized Rosemary Extract Induce Apoptotic Events, Enhances the Anticancer Effects in Breast Cancer - K. Gouthamchandra; H. V. Sudeep; H. B. Lingaraju; K. Shyam Prasad (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
Background: Rosemary (Rosmarinus officinalis) is renown medicinal herb indigenous to Mediterranean region. Rosemary extracts provide a major source of secondary metabolites usually used in food and to make medicine. Objectives: The main objective of the present research was to investigate the anticancer property of standardized rosemary extract in human malignant breast cancer cell by assessing its effect on apoptosis. Materials and Methods: Standardized rosemary extract was evaluated for cytotoxicity using MTT assay, while Fluorescence microscopy evaluated the apoptotic effects of standardized extracts in breast cancer cells using acridine orange/propidium iodide dyes. Subsequently, flow cytometry and western blotting were carried out to assess the apoptotic effect of standardized rosemary extract. Results: The standardized rosemary extracts demonstrated significant cytotoxic effect against MCF-7 with IC50 values of 50.75µg/mL, Fluorescence microscopy and Annexin V-propidium iodide double-staining showed that standardized rosemary extract potentiates apoptosis. On the other hand, western blotting results showed upregulation of proapoptotic proteins, activation of PARP-1, Caspase 9 and concentration dependent decrease in the expression of anti-apoptotic protein Bcl-2 with a related increase in the expression level of proapoptotic protein BAX. Conclusion: In conclusion standardized rosemary extract mediated through the suppression of cell growth and the induction of apoptosis in breast cancer cells. Thus, it has the capability to be developed as an anticancer agent to subside the progression of cancer; however, substantial studies are required.